A Comparative Study of Various Returns on Mutual Funds in India - Mr. Rahul Chauhan; Mr. Neel Rajpurohit (International Journal on Economics, Finance and Sustainable Development, 2021)
The history of mutual funds dates support to 19th century when it was introduced in Europe, in particular, Great Britain. Robert Fleming set up in 1868 the first investment trust called Foreign and colonial investment trust which promised to manage the finances of the moneyed classes of Scotland by scattering the investment over a number of different stocks. This investment trust and other investment trusts which were afterward set up in Britain and the U.S., resembled today’s close – ended mutual funds. The first mutual fund in the U.S., Massachusetts investor’s trust, was set up in March 1924. This was the open – ended mutual fund.